Case–Control Study on Exercise-Induced Vasculitis in Hikers. (August 2022) - Quéneau, Alexandre; Pistorius, Marc-Antoine; Connault, Jérôme; Raimbeau, Alizée; Gautier, Giovanni; Bergère, Guillaume; Artifoni, Mathieu; Durant, Cécile; Bénichou, Antoine; Hersant, Jeanne; Espitia, Olivier
The aim of this study was to identify clinical factors associated with exercise-induced vasculitis (EIV). This study included EIV cases and controls matched for age. Cases included were all members of a hiking club and participated in extended hiking trips. Exercise-induced vasculitis was diagnosed based on clinical signs occurring only after prolonged walks. Chronic venous disease was defined using the Clinical Etiological Anatomical Pathophysiologic classification. This study included 162 hikers: 32 EIV cases and 130 matched controls. Mean age at EIV diagnosis was 47.1 years and 24 (75.0%) of EIV cases were women. Chronic venous disease was present in 19 (57.6%) of EIV cases vs 39 (30.0%) in controls ( P = .001); those with EIV had significantly more saphenous vein insufficiency and C3 venous insufficiency than controls, 85.0 vs 52.6% and 8 (25.0%) vs 13 (10.0%) ( P = .02), respectively. For EIV cases, mean walking distance per hike was significantly higher than for controls ( P = .002). Exercise-induced vasculitis symptoms were typical with rash and/or purpura on the leg in warm conditions. Lesions spontaneously disappear in <10 days. In this study, EIV cases had more chronic venous disease and longer mean walking distances than controls.